Reversal of Bioprosthetic Aortic Valve Thrombosis Using Rivaroxaban—A Case Report - Sharma, Harish; Vetrugno, Vincenzo; Ludman, Peter (Frontiers in Cardiovascular Medicine, 2020)
Background: Bioprosthetic valve thrombosis (BPVT) is a rare but recognised complication causing valve dysfunction. In subacute valve thrombosis, systemic oral anticoagulation is recommended. However, there is little data comparing the efficacy of warfarin and novel oral anticoagulant (NOAC) therapy in this setting. Case Summary: A patient developed subacute BPVT 11 years post-implantation. The patient was initially treated with warfarin for a period of 6 months, with limited effect. Following replacement of warfarin with rivaroxaban, there was significant reversal of the BPVT, as represented by a reduction in transaortic maximal velocity (Vmax) from 4.1m/s to 3m/s over 7 months. Discussion: Systemic oral anticoagulation can be an effective treatment for subacute valve thrombosis. Guidelines currently recommend warfarin as first line but NOACs can be considered in such patients and may be more effective than warfarin. Randomised controlled trials are required to further establish the optimal anticoagulation for patients with subacute BPVT.